Structural Response of Concrete Buildings to Seismic and Wind Loads in Bangladesh Using ETABS and BNBC 2020 - Aziz, Mohammad Abdul; Rahman, Sajedur; Ghosh, Avishek; Mazumdar, Mohammad Hasan Mahmud; Haque, Akramul; Ovi, Fahmida Khanam (Disaster in Civil Engineering and Architecture, 2026)
Rapid urbanization in Bangladesh has led to an increasing demand for multi-storey buildings, necessitating robust structural design to resist lateral loads from both earthquakes and wind. This study analyzes the seismic and wind load performance of G+8 reinforced concrete (RC) building located in four different seismic zones of Bangladesh, using ETABS 2017 in compliance with the Bangladesh National Building Code (BNBC) 2020. The structure was evaluated under both seismic (EQX, EQY) and wind (WX, WY) loads. The structural analysis revealed that wind loads (WX and WY) consistently govern the lateral design for this structure, as evidenced by storey shear (peaking at 45 Kip at the base in Zone 4 and storey displacement (WX peaking at 8 in) and drift (WX peaking at 0.09 in) being substantially higher than seismic demands. Although base shear linearly increased almost threefold from Zone 1 (33.28 Kip) to Zone 4 (99.84 Kip) due to rising seismic zone coefficients, the wind forces dominate the serviceability checks. Maximum storey displacement and drift were concentrated in Zones 3 and 4, with the latter exhibiting the highest drift (0.065 in WX) and extreme torsional irregularity, peaking at 7.82 in WX. The analysis confirms that both seismic and wind effects significantly influence building performance, with seismic forces dominating in higher zones and wind-induced displacements being critical in specific directions. This underscores the importance of region-specific design considerations to ensure structural safety and serviceability in Bangladesh’s diverse seismic landscape.